العنـف في الوســــط التعليمي ووسائل الحد منه - الوقاية والعلاج - منصور, مصطفى; بن خليفة, اسماعيل (جامعة الوادي - University of Eloued, 2018)
العنف بشكل عام، قضية كبرى، عرفها الإنسان منذ بدء الخليقة ,كما أن العنف هو أحد القوى التي تعمل على الهدم أكثر من البناء في تكوين الشخصية الإنسانية ونموها، وهو انفعال تثيره مواقف عديدة، ويؤدي بالفرد إلى ارتكاب أفعال مؤذية في حق ذاته أحيانا وفي حق الآخرين أحياناً أخرى. وعلى الرغم منأهمية دراسة الباحثين لموضوع العنف في شتى مجالات الحياة، فإن ما يمارس من عنف في مؤسساتنا التعليمية لم ينل الحظ الكافي من الدراسة والتحليل، لتشخيص هذه الظاهرة بشكل دقيق فقد كان التركيز على مظاهر العنف التي يمارسها المربي على المتعلم وهذه زاوية نظر للمشكلة قد يشوبها بعض القصور في استيعاب كل أبعاد الظاهرة حيث يرى " بول فولكي " في قاموسه التربوي أن العنف هو اللجوء غير المشروع إلى القوة وأضاف اليه" أندري لالاند " أن العنف يمكن أن يكون رمزيا بالكلمة العنيفة وخاصة في مرحلة المراهقة التي يمر بها التلاميذ، بصفتها مرحلة انتقالية من الطفولة إلى الرشد، يرافقها كثير من التغييرات الجسدية والنفسية والتي تترك آثارها العميقة في شخصية الفرد، وتكيفه مع المؤسسة والمجتمع والبيئة المحيطة به,وبهدف ضمان بيئة سليمة وآمنة تجسد قيم الحوار و تدعم الاساليب المتحضرة في التعبير عن الراي المخالف تأتي هذه الدراسة للإجابة عن التساؤلات التالية : • ماهي أهم مظاهر العنف في الوسط التعليمي ؟ وماهي الاسباب التي أدت الى وجود هذه الظاهرة ؟ • ماهي أهم استراتيجيات الوقاية من هذه الظاهرة ؟ للحد من آثارها السلبية قبل خروجها عن السيطرة. • ماهي أساليب العلاج المتاحة للتدخل و الحلول الممكنة لهذه الآفة الاجتماعية التي أحاطت بمدارسنا ؟ وعلى هذا الأساس سنعرض لقضية العنف في الوسط التعليمي محاولين تقديم مقترحات تسهم في فهم واستيعاب هذه الظاهرة وتحقق السيطرة عليها داخل مؤسساتنا التعليمية.Violence, in general, is a major issue that man has known since the beginning of creation. Violence is one of the forces that destroy more than the construction of human personality and growth, an emotion aroused by many situations, And leads the individual to commit harmful acts against himself sometimes and sometimes against others. Despite the importance of researchers studying the subject of violence in various areas of life, the violence practiced in our educational institutions has not received sufficient study and analysis to diagnose this phenomenon accurately, the focus was on the manifestations of violence practiced by the educator on the learner and this is a view of the problem may be deficient in some deficiencies in the absorption of all dimensions of the phenomenon. In his educational dictionary, Paul Volcki argues that violence is the illegal recourse to force. Andre Laland added that violence can be symbolic in a violent word, especially in adolescence, as a transition from childhood to adulthood, accompanied by many Of the physical and psychological changes that have a profound impact on the personality of the individual and its adaptation to the institution, society and the surrounding environment. In order to ensure a safe and secure environment that embodies the values of dialogue and supports civilized methods of expressing dissenting opinion, this study answers the following questions: • What are the most important manifestations of violence in the school? What are the reasons for this phenomenon? • What are the most important strategies to prevent this phenomenon? To reduce their negative effects before they are out of control. • What treatment methods are available for intervention and possible solutions to this social scourge that surrounded our schools? On this basis, we will present the issue of violence in the educational environment, trying to make proposals that contribute to understand this phenomenon and control it within our educational institutions.
Violence in the educational environment and means of reducing itPrevention and treatment
مقال
Keywords: العنـف , الوسط التعليمي,الوقاية , العلاج; violence, education, Prevention, treatment